COVERAGE, ACCESS, AND MEDICAID: New Strategies, Similar Results: New Hampshire's Experience with Medicaid Work Requirements. (20th August 2020) - Hill, I.; Burroughs, E.; Adams, G.
Abstract : In June 2019, New Hampshire began requiring beneficiaries to report work and community engagement hours as a condition of eligibility for its Medicaid expansion program, Granite Advantage, becoming the second state to do so following Arkansas's program implemented a year earlier. State officials set out to design and implement a program that would avoid the problems in Arkansas that resulted in over 18, 000 Medicaid adults being disenrolled in the first six months of Arkansas Works. But after just one month, New Hampshire officials realized they had not succeeded in reaching and informing the target population, and 17, 000 Granite Advantage enrollees were scheduled to receive letters saying they were out of compliance with Medicaid work rules and faced the prospect of losing coverage. However, state officials suspended the program before this occurred, and federal courts subsequently halted the program indefinitely. We studied New Hampshire's Medicaid work requirement program to understand how it was implemented and why, like Arkansas, it apparently failed to promote work and threatened coverage. Building on a similar case study of Arkansas Works conducted earlier in 2019, we visited New Hampshire for three days in October 2019, conducting seven interviews with 13 stakeholders and two focus groups with 11 Medicaid enrollees to learn about the state's program and its effects on beneficiaries. Nineteen additional interviews were conducted by telephone. Medicaid beneficiaries enrolled in Granite Advantage, New Hampshire's Medicaid expansion program. Regarding outreach, New Hampshire allowed insufficient time and funding to publicize and educate beneficiaries about new work rules and relied too heavily on mail‐ and telephone‐based methods that failed to connect with a hard‐to‐reach population. In attempting to promote work, the state's Granite Workforce pilot was crippled by very limiting eligibility requirements and a short, six‐month implementation period that helped just 120 enrollees while spending less than 13% of its budget allocation. Like Arkansas, New Hampshire tried to proactively exempt many members from work requirements (eg, those already working 100 hours/month, satisfying SNAP work requirements, who are disabled, pregnant, or caring for children under six). But also, like Arkansas, the state failed to use health plan claims data to identify "medically frail" individuals who experienced difficulties applying for exemptions. New Hampshire designed a "no wrong door" approach for reporting work and community engagement that, unlike Arkansas's primarily online system, allowed people to report hours online, by mail, over the phone, or in‐person. However, the system was fraught with problems and only a fraction of beneficiaries was able to successfully report hours. Despite intentional efforts to design a "better" program than Arkansas's, New Hampshire's Medicaid work requirements produced nearly the same result in a fraction of the time, facing the disenrollment of a large share—67 percent—of persons subject to the requirement. Based on the experiences of the first two states to implement Medicaid work requirements—states that adopted considerably different approaches under different circumstances—evidence suggests that such programs cause significant harm to Medicaid beneficiaries while not appreciably supporting their ability to work. The Robert Wood Johnson Foundation.